Analysis of The Vertical and Horizontal Type Cultivator Claw On The Performance Test of The Power Weeder Machine - Prasetiyo, Angger Bagus; Sekarjati, Kartinasari Ayuhikmatin (Universitas Muhammadiyah Jakarta, 2024)
Weeds account for approximately 40–65% of rice production losses and affect 15–42% of arable land. If not managed promptly, crop yields could be drastically reduced. Traditional weed control methods, including manual weeding, chemical, semi-mechanical, and mechanical techniques, vary in effectiveness and efficiency. Conventional chemical and semi-mechanical methods are often less effective, costly, time-consuming, and environmentally detrimental. Thus, mechanical weed control presents a superior alternative. This study aims to compare the performance of power weeder machines equipped with vertical and horizontal cultivator claws in terms of weeding time, tool efficiency, and plant damage. The experiment was conducted on 30-day-old rice plants, with each test performed four times over a 1 x 6-meter area, maintaining a muck depth of 20 cm between rice plants. The power weeder machines were equipped with eight claws per unit, a 1.5 HP drive motor, and operated on a mix of oil and petrol fuel. Results indicate that the vertical-type cultivator claw achieved a work efficiency of 72.42%, while the horizontal-type cultivator claw achieved 86.04%. Weeding effectiveness was 93.10% for horizontal claws and 94.77% for vertical claws. Post-weeding, the horizontal cultivator claws caused 14.13% damage to rice plants, compared to 5.73% for vertical claws. Given its high weeding efficiency and minimal plant damage, the vertical type claw cultivator is highly recommended.